Pengaruh Usia, Berat Badan, Tinggi Badan Dan Indeks Massa Tubuh Terhadap Gula Darah Sewaktu - Solehudin, Solehudin; Syabanasyah, Inas (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Mellitus (DM) is one of the metabolic diseases whose prevalence continues to increase, both globally and in Indonesia. This increase in prevalence is caused by various factors, such as changes in lifestyle, unhealthy diet, and lack of physical activity. This study aims to analyze the effect of age, weight, height, and Body Mass Index (BMI) on random blood sugar levels. The study used a cross-sectional design with 117 respondents selected through the Slovin method in one of the neighborhood associations in Bogor City. Data were collected using observation and physical measurements, and analyzed by multivariate linear regression using Jamovi 2.2.5 software. The results showed that age had a significant effect on random blood sugar levels (p = 0.001), with a regression coefficient of 2.17. In contrast, weight, height, and BMI did not show a significant relationship. These findings indicate that every 1-year increase in age can increase random blood sugar levels by 2.17 units. This phenomenon can be explained by decreased insulin sensitivity, decreased pancreatic beta cell function, and lower basal metabolic rate in the elderly. In conclusion, age is a significant factor that affects random blood sugar levels, while other variables, such as weight, height, and BMI, are influenced by external factors not included in the model. This study emphasizes the importance of interventions that focus on preventing DM through community education, healthy lifestyle management, and regular physical activity, especially in the elderly.